Microsatellite and Chromosome Evolution of Parthenogenetic Sitobion Aphids in Australia - Sunnucks, P. (1996)
Single-locus microsatellite variation correlated perfectly with chromosome number in Sitobion miscanthi aphids. The microsatellites were highly heterozygous, with up to 10 alleles per locus in this species. Despite this considerable allelic variation, only seven different S. miscanthi genotypes were discovered in 555 individuals collected from a wide range of locations, hosts and sampling periods. Relatedness between genotypes suggests only two successful colonizations of Australia. There was no evidence for genetic recombination in 555 S. miscanthi so the occurrence of recent sexual reproduction must be near zero. Thus diversification is by mutation and chromosomal rearrangement alone. Since the aphids showed no sexual recombination, microsatellites can mutate without meiosis. Five of seven microsatellite differences were a single repeat unit, and one larger jump is likely. The minimum numbers of changes between karyotypes corresponded roughly one-to-one with microsatellite allele changes, which suggests very rapid chromosomal evolution. A chromosomal fission occurred in a cultured line, and a previously unknown chromosomal race was detected. All 121 diverse S. near fragariae were heterozygous but revealed only one genotype. This species too must have a low rate of sexual reproduction and few colonizations of Australia.